Development and Validation of Pandemic Stressor Scale for Students - Waqar Ali, Rubina Hanif, Ayesha Saeed Butt (PJE, 2023)
The current study aims to develop and validate the Pandemic Stressor Scale through Exploratory Factor Analysis (EFA) and the factors explored is confirmed through Confirmatory Factor Analysis (CFA). EFA sample comprised of university students (n = 300) in which male (n = 195) and female (n = 105) age ranged 18 to 28 years (M= 21.84 and SD =1. 88). A factor loading of.30 was established as the standard for choosing an item for the scale. Direct oblimin rotation method was used, as a result EFA presented four meaningful factors for Pandemic Stressor scale and factors named as Online learning stressor (9 items), Goal Achievement Hassles (8 items), Academic Hassles (10 items), and Mental Health Issues (12 items). For CFA total sample of university students (n = 300), male sample (n =108) and female sample (n =192) age ranged 18 to 26 years (M=21 and SD =1.54) were taken and confirmed the factors structure of Student Stressor Scale. Alpha reliability for the Pandemic Stressor Scale was calculated, it was .92. Overall Pandemic Stressor Scale for Students emerges as reliable and valid measure to assess the Student Stressor during the pandemic in Pakistani culture.